P605 Real life efficacy of tofacitinib in different situation in ulcerative colitis: a retrospective worldwide multicentre collaborative study. (30th January 2023) - Resál, T; Bacsur, P; Bor, R; Bálint, A; Katsanos, K; Michalopoylos, G; Ribaldone, D G; Attauabi, M; Mirabella, Z; Yanai, H; Bezzio, C; Castiglione, F; et al.
Abstract: Background: The orally administered small molecule drug pan-Jak inhibitor tofacitinib (TFB) appears to be effective in the treatment of ulcerative colitis (UC), however, available real world studies are limited by the cohort size. In addition, TFB may also be efficacious in patients with acute severe colitis (ASUC) as a rescue therapy. We aimed to conduct an international cohort study, to investigate the efficacy and safety of TFB in patients with moderate to severe colitis and ASUC. Methods: This was a retrospective, international multi-centre, cohort study including 23 tertiary referral centres. UC patients with at least 6 weeks of TFB treatment were included. Physicians categorized the indication as rescue therapy (RT) and chronic activity (CA). Baseline demographic and clinical data, clinical/endoscopic activity indexes, laboratory parameters (including CRP, faecal calprotectin, liver enzymes, lipids, iron homeostasis), adverse events, and hospitalization/colectomy rates were collected at w0, w2-6, w8-14, w22-30 and w48-56 intervals. Steroid-free remission, colectomy rates, primary non-response (PNR) and loss-of response (LOR) rates, and safety was studied. Results: A total of 391 UC patients (mean age: 39.2±14.1 years, male/female ratio 208/183; mean follow-up period 33.7±18.1 weeks) were included. 107 patients (27.4%) received TFB as a rescue therapy. Most of the patients received it as a third line treatment (37.4%). Steroid-free remission (SFR) rates were 21.3% (RT: 25.0%, CA: 22.3%) at w14, and 40.1% (RT: 32.5%, CA: 42.2%) at w52. In total, baseline pMayo (OR: 0.856; p=0.007) was negatively associated with w12 SFR, while line of treatment (OR: 0.749; p=0.047) and age (OR: 1.022; p=0.038) influenced the w52 SFR in the CA group. The w12 colectomy rate was 5.1%, and no difference was observed between groups (RT: 8.5%; CA: 3.8%), however, w52 colectomy rate was higher in the RT group (19.2% compared to 5.9%; p<0.001). Line of treatment (OR: 1.66; p=0.036) and age (OR: 0.94; p=0.005) were associated as well with w52 colectomy rate. Mucosal healing (eMayo≤1) rate increased from 3.9% to 43.0% (p<0.001). PNR rate was 22.5% and LOR 54.4%. In total, 67 adverse events (17.1%) were reported, and 17.9% of them were resulted in cessation of the treatment. Thromboembolic event was reported in 1 case, however, this patient had concomitant malignancy. Conclusion: TFB is effective in both moderate to severe UC, and in patients with ASUC as a rescue therapy. TFB treatment resulted in high rates of SFR and mucosal healing in short- and long term even after anti-TNF and vedolizumab failure. Higher baseline disease activity and number of previous biological therapies negatively influenced efficacy. Serious adverse events were rare.